2022
DOI: 10.1021/acsfoodscitech.2c00193
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Light-Emitting Diode Illuminations on Bioactive Compounds in Ruby Streaks Mustard Microgreens by Ultra-High Performance Liquid Chromatography–High-Resolution Mass Spectrometry

Abstract: Mustard (Brassica juncea var. “Ruby Streaks”) is a popular microgreen species with rich phenolic and glucosinolate contents. Light-emitting diodes (LEDs) have been increasingly used to promote the content of bioactive compounds in commercially grown plants, particularly in controlled environment agriculture (CEA) settings. The present research aimed to investigate the effect of LED light wavelengths on the phytochemical profiles of the major secondary metabolites [i.e., anthocyanins, non-anthocyanin phenolics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…"ruby streaks", RS) is a popular species consumed as microgreens or baby leaves, both of which are considered excellent sources for phytonutrients. 13,14 RS microgreens were found in our previous study to respond significantly to blue and red lights in terms of yield, color, morphology, and metabolomic profile. 13 Related, mature red leaf mustard (B. juncea L.) was recently found to show larger leaves and higher fresh yield with 1% FR in the spectrum compared to 11% FR.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…"ruby streaks", RS) is a popular species consumed as microgreens or baby leaves, both of which are considered excellent sources for phytonutrients. 13,14 RS microgreens were found in our previous study to respond significantly to blue and red lights in terms of yield, color, morphology, and metabolomic profile. 13 Related, mature red leaf mustard (B. juncea L.) was recently found to show larger leaves and higher fresh yield with 1% FR in the spectrum compared to 11% FR.…”
Section: Introductionmentioning
confidence: 75%
“…13,14 RS microgreens were found in our previous study to respond significantly to blue and red lights in terms of yield, color, morphology, and metabolomic profile. 13 Related, mature red leaf mustard (B. juncea L.) was recently found to show larger leaves and higher fresh yield with 1% FR in the spectrum compared to 11% FR. 5 However, it remains unknown (1) whether the RS cultivar responds significantly to FR in terms of yield, morphology, and phytonutrient composition, (2) whether such responses persist or vary at different growth stages, and (3) whether RS responds differently to FR applied singularly versus FR supplemented with white light treatment.…”
Section: Introductionmentioning
confidence: 75%
“…In contrast, Brassica juncea species (red mustard, Dijon mustard, and wasabi microgreens) showed the lowest glucosinolates content. The most abundant glucosinolates in mustard microgreens are sinigrin, glucobrassicin, gluconapin, 4-hydroxyglucobrassicin, and 4-methoxyglucobrassicin. , Aliphatic glucosinolates are predominant compounds in broccoli microgreens. Glucoraphanin, glucoiberin, and glucoerucin are the primary glucosinolates present in broccoli microgreens. , Broccoli microgreens contain more glucoerucin and glucoraphanin glucosinolates than broccoli florets and mature broccoli leaves .…”
Section: Composition Of Bmmentioning
confidence: 99%
“…59,65 Anthocyanins are water-soluble pigments among the phenolic compounds that are not only responsible for the color of fruits and vegetables but also play a role in disease prevention. Recently, the study of Liu et al 68 reported the presence of 26 anthocyanins in mustard microgreen, of which 18 of them are acylated cyanidin (Cy)-3-O-sophoroside-5-Odiglucosides and eight are acylated Cy-3-O-sophoroside-5-Oglucosides. In another study, 30 different anthocyanins (only cyanidin derivatives) that contribute colors to red cabbage, red mustard, purple mustard, and purple kohlrabi microgreens were reported by Sun et al 65 Cyanidin-3-(feruloyl)(sinapoly)dihexoside-5-hexoside was identified by Kyriacou et al 20 as the most abundant anthocyanin component in mibuna, pak choi, mizuna, and komatsuna microgreens.…”
Section: Vitaminsmentioning
confidence: 99%
See 1 more Smart Citation